Inter-rater reliability of theAction Research arm test & Upper limb related fugel meyer test in Adult with CVA from qazvin - Elham Karimi; Minoo Kalantary; Zahra shafiee; seyed mahdi Tabatabaiee (Vesnu Publications, 2014)
Introduction:Stroke is one of the most common life-threatening neurologic disorders and is among the most important causes of disability in adult life.Unilateral upper limb motor impairment is one of the main causes of dependence in activity of daily living. Action Research arm test &Upper limb related fugel meyer test evaluates upper limb motor performance of a hemiplegic patient. The aim of this study was to demonstrate inter-rater reliability of the tests. Materials and methods: In this analytic and reliability study, 20 patients with CVA aged from 40 to 65, selected form occupational therapy clinics& rehabilitation center in Qazvin based on convenience sampling were tested by two occupational therapists in one session. SPSS 18 and ICC test was used for data analysis (α=0.05). Results: the ICC test was calculated and equalled to 0/972(ARAT),0/977(FMT) (p<0.05 ) Conclusion:ARAT &fugel meyer test inter-rater reliability is acceptable to be used for CVA patients